Exercise in preventing falls and fall related injuries in older people: a review of randomised controlled trials. Issue 1 (1st February 2000) - Gardner, Melinda M; Robertson, M Clare; Campbell, A John
Abstract : Objective —To assess the effectiveness of exercise programmes in preventing falls (and/or lowering the risk of falls and fall related injuries) in older people. Design —A review of controlled clinical trials designed with the aim of lowering the risk of falling and/or fall injuries through an exercise only intervention or an intervention that included an exercise component Main outcome measures —Falls, fall related injuries, time between falls, costs, cost effectiveness. Subjects —A total of 4933 men and women aged 60 years and older. Results —Eleven trials meeting the criteria for inclusion were reviewed. Eight of these trials had separate exercise interventions, and three used interventions with an exercise programme component. Five trials showed a significant reduction in the rate of falls or the risk of falling in the intervention group. Conclusions —Exercise is effective in lowering falls risk in selected groups and should form part of falls prevention programmes. Lowering fall related injuries will reduce health care costs but there is little available information on the costs associated with programme replication or the cost effectiveness of exercise programmes aimed at preventing falls in older people.